New horizons in the implementation and research of comprehensive geriatric assessment: knowing, doing and the “know-do” gap - Gladman, John R.F.; Conroy, Simon P.; Ranhoff, Anette H.; Gordon, Adam L. (Oxford University Press, 2016)
In this paper we outline the relationship between the need to put existing applied health research knowledge into practice (the “know-do gap”) and the need to improve the evidence base (the “know gap”) with respect to the health care process used for older people with frailty known as comprehensive geriatric assessment (CGA). We explore the reasons for the know-do gap and the principles of how these barriers to implementation might be overcome. We explore how these principles should affect the conduct of applied health research to close the know gap. We propose that impaired flow of knowledge is an important contributory factor in the failure to implement evidence-based practice in comprehensive geriatric assessment; this could be addressed through specific knowledge mobilisation techniques. We describe that implementation failures are also produced by an inadequate evidence base which requires the co-production of research, addressing not only effectiveness but also the feasibility and acceptability of new services, the educational needs of practitioners, the organisational requirements of services, and the contribution made by policy. Only by tackling these issues in concert and appropriate proportion, will the know and know-do gaps for CGA be closed.